Application of Soil Washing and Thermal Desorption for Sustainable Remediation and Reuse of Remediated Soil - Sang-Hwan Lee (MDPI AG, 2021)
Global governance of soil resources as well as revitalizations and remediation of degraded areas seem to be necessary actions for sustainable development. A great deal of effort has gone into developing remediation technologies to remove or reduce the impact of these contaminants in the environment. However, contaminated soil remediations in stringent conditions deteriorate soil properties and functions and create the need for efficient soil revitalization measures. Soil washing (SW) and thermal desorption (TD) are commonly used to remediate contaminated soil and can significantly reduce the contaminant, sometimes to safe levels where reuse can be considered; however, the effects of treatment on soil quality must be understood in order to support redevelopment after remediation. In this review, we discussed the effects of SW and TD on soil properties, including subsequent soil quality and health. Furthermore, the importance of these techniques for remediation and reclamation strategies was discussed. Some restoration strategies were also proposed for the recovery of soil quality. In addition, remediated and revitalized soil can be reused for various purposes, which can be accepted as an implementation of sustainable remediation. This review concludes with an outlook of future research efforts that will further shift SW and TD toward sustainable remediation.